How to talk so kids will listen & listen so kids will talk: a randomized controlled trial evaluating the efficacy of the how-to parenting program on children's mental health compared to a wait-list control group - Mireille Joussemet; Geneviève A. Mageau; Marie-Pier Larose; Mélanie Briand; Frank Vitaro (BMC, 2018)
Abstract Background Basic parenting research reveals that child mental health is associated with optimal parenting, which is composed of three key dimensions (structure, affiliation and autonomy support). The present study aims to test the efficacy of the parenting program "How to talk so kids will listen & listen so kids will talk" (French version), thought to address all of these dimensions, in promoting children's mental health. We predict that the How-to Parenting Program will promote child mental health by fostering optimal parenting. Methods In this randomized controlled trial (RCT), the seven-week parenting group was offered to parents of 5- to 12-year-old children, in their local grade school. Children's mental health assessments were questionnaire-based (parent, child and teacher reports) and took place at pre- (T1) and post- (T2) intervention as well as at 6-month (T3) and 1-year (T4) follow-ups. We compared children whose parents took part in the program with children whose parents did not take part in it until the completion of the trial (i.e., 1 year wait-list control groups). The primary outcome is children's psychological problems (externalizing and internalizing). Secondary outcomes include parenting, the putative mediator of the expected benefits of the program on child mental health, as well as positive indicators of child mental health (strengths and subjective well-being) and parents' own mental health. Discussion To our knowledge, this is the first RCT to test the efficacy of the "How to talk so kids will listen & listen so kids will talk" program in promoting child mental health. In addition to the close correspondence between basic parenting research and the selected program, strengths of this study include its feasibility, monitoring of potentially confounding variables, ecological validity and inclusion of positive indicators of mental health. Trial registration Current clinical trial number is NCT03030352. Ongoing study, retrospectively registered on January 2017. No amendment to initial protocol.